LINGKUNGAN KERJA BERPENGARUH TERHADAP KINERJA PEGAWAI DI DINAS PERPUSTAKAAN DAN ARSIP KABUPATEN TANGERANG - Galuh Lutfi Fadil; Yusmedi Yusuf; Seno Santoso (JURNAL ILMIAH ILMU ADMINISTRASI, 2019)
This research aims to describe and analyze The Influence of the Work Environment on Employee Performance in The Library and Archives Service in Tangerang District. The population in this study amounted to 48 respondents, the sampling technique used was the saturation sampling technique (census). Respondents in this study were the Library and Archives Service in Tangerang District. The research method used is a quantitative-associative method. Then the data were analyzed using the SPSS (Statistical Product and Service Solution) for windows version 21.0 using the correlation technique with the Pearson product moment method and then proceed with regression and hypothesis testing. The results in this study are "There is a Positive and Significant Effect Between the Work Environment on the Performance of Employees in the Tangerang District Library and Archives Office". Based on obtaining the calculated t value of 7.141 while the value in t table is 2.013. Thus, according to the calculation of the statistical hypothesis if the value (7,141)> (2,013), then Ho is rejected and Ha is accepted. Keywords : Work Environment, Employee Performance, Library and Archives.